Multi Peran Guru di SMP Negeri 1 Konawe Selatan (Antara Kinerja dan Panggilan Moral) - Sandra Hasba (Institut Agama Islam Negeri (IAIN) Kendari, 2019)
This article aims to provide an overview of the roles of teachers in improving performance in SMP Negeri 1 Konawe Selatan, which includes: 1) The role of teachers in creating a learning climate; 2) Factors that affect teacher performance; 3) Portrait of the teacher at SMP Negeri 1 Konawe Selatan; 4) the role of the principal in improving teacher performance. This research uses descriptive qualitative research, where the process of collecting data is done through interviews, observations, and documentation studies. Data analysis is performed through the stages of reduction, display, and data verification. The results showed that the learning climate in SMP Negeri 1 Ranomeeto was created because of the high involvement of the teachers. The ability, motivation and skill factors greatly affect the performance of teachers in SMP Negeri 1 Konawe Selatan. Teacher roles performed by teachers in SMP Negeri 1 Konawe Selatan have exceeded their performance obligations. The headmaster became a mover in expanding roles and improving teacher performance in SMP Negeri 1 Konawe Selatan. Keywords: Performance, Teacher Competence, Leadership